Global perspectives and hotspots of VEGF signaling pathway in liver disease from 2008 to 2023: A bibliometric analysis and visualization - Yi He; Jiaxin Huang; Xiaofan Liang; Chang Shao; Xiguang Sun; Junjie Zhang (Heliyon)
Background: The vascular endothelial growth factor (VEGF) signaling pathway is closely related to pathological angiogenesis in liver disease. Anti-angiogenesis is an effective intervention in the clinical treatment of liver disease. Some antiangiogenic drugs are resistant and have limitations in clinical use. Methods: This research uses bibliometric methods to assess the literature on the VEGF signaling pathway in liver disease from 2008 to 2023. Results: The number of publications has generally increased over the past 16 years, meaning that enormous researchers are interested in this field. China and the USA have published the most articles and cooperate closely with each other. Plos one has published the largest number of articles in this area, and Hepatology and Journal of Hepatology is the most authoritative journal. Llovet JM is an outstanding researcher in the field with the highest citations. Keywords and research hotspots analysis indicated that researchers are very concerned about the application and clinical research status of anti-angiogenic drugs in hepatocellular carcinoma (HCC). Continuing to deepen the research on the use of anti-angiogenic drugs alone and in combination is necessary. In addition, the resistance of anti-angiogenic therapeutic drugs leads to a complex mechanism of angiogenesis response caused by hypoxia, which requires further research. Conclusions: This study analyzed the research situation related to the VEGF signaling pathway in liver disease from a bibliometric and visual perspective. Our analysis helps researchers better understand the research directions and hotspots in this area, enabling them to better carry out research in the future.